Depressive Symptoms, Chronic Pain, and Falls in Older Community-Dwelling Adults: The MOBILIZE Boston Study - Eggermont, Laura H.P. (2012)
BACKGROUND: A better understanding is needed about the role of depression and chronic pain, two related chronic conditions, as predictors of falls in older persons. OBJECTIVES: To examine whether overall depressive symptoms and symptom clusters are associated with fall risk, and to determine whether chronic pain mediates the relationship between depression and fall risk in aging. DESIGN: Prospective cohort study. SETTING: City of Boston and surrounding communities. PARTICIPANTS: Older community-dwelling adults (n=722,mean age 78.3y). MEASUREMENTS: Depressive symptomatology was assessed at baseline by the CESDR as overall depression and two separate domains, cognitive or somatic symptoms. Chronic pain was examined at baseline as: number of pain sites (none, single site, or multisite/widespread), pain severity, and pain interference with daily life activities. Participants recorded falls on monthly postcards during a subsequent 18-month period. RESULTS: By using negative binomial regression, the rate of incident falls was highest among those with highest burden of depressive symptoms (indicated by total CESDR, Cognitive or Somatic CESDR domains). After adjustment for multiple confounders and fall risk factors, fall rate ratios comparing the highest CESDR three quartiles to the lowest quartile were 1.91, 1.26, 1.11, respectively. Similarly graded associations were observed according to CESDR domains. Although pain location and interference were mediators of the relationship between depression and falls, adjustment for pain reduced fall risk estimates only modestly. There was no interaction between depression and pain in relation to fall risk. CONCLUSION: Depressive symptoms are associated with fall risk in older adults and are mediated in part by chronic pain. Research is needed to determine effective strategies for reducing fall risk and related injuries in older people who have pain and depressive symptoms.